PENGARUH PROMOSI, BRAND IMAGE DAN KUALITAS PRODUK TERHADAP BRAND LOYALTY DETERJEN MEREK RINSO DI KELURAHAN TANJUNG SENGKUANG KOTA BATAM - WULANDARI, MEILANI; Dr. Suhardi S. E. M. M (SCIENTIA JOURNAL, 2022)
This study aims to determine the effect of promotion, brand image and quality on consumer loyalty Rinso brand detergent. Collecting data using a questionnaire distributed to respondents totaling 100 samples using Rinso detergent. The sampling technique in this study uses the accidental sampling technique where all people who coincidentally meet with the researcher can be sampled if it is felt that the sample encountered meets certain characteristics needed by the researcher. The analytical method used is descriptive quantitative analysis and quantitative analysis with multiple regression. Partially, the results of this study indicate that promotion and quality have a positive and significant effect on consumer loyalty and brand image has no significant effect on loyalty. Simultaneously, the results showed that the variables of promotion, brand image and quality had a significant effect on consumer loyalty.Keywords: Promotio, Brand Image, Quality; Customer Loyalty.